Dynamic energy balanced max flow routing in energy-harvesting sensor networks - Bin Cai; Shan-Li Mao; Xiao-Hui Li; Yue-Min Ding (International Journal of Distributed Sensor Networks)
We propose a dynamic energy balanced max flow routing algorithm to maximize load flow within the network lifetime and balance energy consumption to prolong the network lifetime in an energy-harvesting wireless sensor network. The proposed routing algorithm updates the transmission capacity between two nodes based on the residual energy of the nodes, which changes over time. Hence, the harvested energy is included in calculation of the maximum flow. Because the flow distribution of the Ford–Fulkerson algorithm is not balanced, the energy consumption among the nodes is not balanced, which limits the lifetime of the network. The proposed routing algorithm selects the node with the maximum residual energy as the next hop and updates the edge capacity when the flow of any edge is not sufficient for the next delivery, to balance energy consumption among nodes and prolong the lifetime of the network. Simulation results revealed that the proposed routing algorithm has advantages over the Ford–Fulkerson algorithm and the dynamic max flow algorithm with respect to extending the load flow and the lifetime of the network in a regular network, a small-world network, and a scale-free network.